PERANCANGAN SISTEM INFORMASI E-COMMERCE BERBASIS WEBSITE PADA UMKM "SEKAR GALUH ETNIC" - Muhammad Faiz Hafizh Ramadhan (2023)
SME "Sekar Galuh Etnic" is a SME located in South Jakarta who sell stitch result which is clothes that focused on batik clothes. This SME also take a custom order according customer wishes from size to design of the clothes. This SME has experienced a decrease in the number of orders caused of pandemic and also caused of lack of use of information technology in marketing its products and services. The scope of marketing of this MSE is just mouth to mouth. This research objective is for design a web-base e-commerce information system to expand marketing reach of this MSE. The researcher used waterfall method beacuse this method systematic or sequentially, so that it has a clear sequence flow which can minimize errors on the next step. The software creation used ReactJS which javascript based. The system supported by backend service namely Hasura.io for data tabulation and data storage which PostgreSQL based. The aim of this research to expand marketing reach, digitalized business process, and digitalized data storage. This research produce web base e-commerce for SME "Sekar Galuh Etnic"